(untitled) (Swiss Medical Weekly, 2024)
AIMS OF THE STUDY: Limited knowledge exists regarding exposures to non-therapeutic chemicals by women planning to conceive, or during pregnancy or breastfeeding. The Swiss Teratogen Information Service (STIS) provides information to healthcare professionals about medications and other exposures during pregnancy or breastfeeding. This study aimed to describe the queries on non-therapeutic chemicals addressed to the STIS over the past two decades. METHODS: Using data from the STIS for the years 2000 to 2019, we conducted a descriptive analysis of all queries related to women’s exposures to non-therapeutic chemicals during pregnancy planning, pregnancy or breastfeeding. RESULTS: Over two decades, the STIS database recorded 320 exposures to chemicals. Workplace settings accounted for over 60% of queries, followed by exposures at home (20%). In almost half (48%) of the queries, more than one chemical was mentioned, totalling 885 chemicals across these 320 queries. Commonly mentioned chemicals included isopropanol, acetone and lead. Solvents were the leading category of products (16%), followed by cleaning products (10%), paints (8%) and insecticides (5%). The follow-up data showed five diverse cases of congenital malformations, accounting for 4.0% (5 out of 125) of the sample, a figure in line with the background risk of malformations in the general population. CONCLUSIONS: This study emphasises the importance of conducting research that comprehensively captures the highly heterogeneous exposures to non-therapeutic chemicals during pregnancy and suggests that attention should be given not only to professional settings, but also to domestic contexts.